Analysis of the Dynamics Characteristic of Single Section Train with Considering the Torsional Vibration of Transmission System - Chen Zheming; Wang Lizhang; Yu Yang (Jixie chuandong)
In order to analyze the influence of vibration of transmission system on vehicle dynamics performance,the train drive system is simplified as a series system containing shaft segments and equivalent disc,a whole multi- body dynamics model of a high speed train and a torsional vibration model of transmission system are established,and the calculation and analysis of additional moment produced by torsional vibration is carried out. Regarding the additional moment as the main factor,through the united simulation,the dynamics characteristic of the high speed train under the traction conditions with and without the torsional vibration characteristic of the transmission system are compared and analyzed. The results show that,under traction condition,the torsional vibration of the transmission system has a large influence on the vibration acceleration of the vehicle body in the lateral and vertical direction,and less influence on the carbody longitudinal vibration. The additional torque has large influence on the longitudinal vibration of bogie frame and wheelset. Therefore,in the dynamics analysis of high speed train,taking the torsional vibration characteristics of the transmission system in consideration is more suitable to the real condition of the train operation.